2018
DOI: 10.1093/nar/gky245
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 lysine 36 methyltransferase mobilizes NER factors to regulate tolerance against alkylation damage in fission yeast

Abstract: The Set2 methyltransferase and its target, histone H3 lysine 36 (H3K36), affect chromatin architecture during the transcription and repair of DNA double-stranded breaks. Set2 also confers resistance against the alkylating agent, methyl methanesulfonate (MMS), through an unknown mechanism. Here, we show that Schizosaccharomyces pombe (S. pombe) exhibit MMS hypersensitivity when expressing a set2 mutant lacking the catalytic histone methyltransferase domain or a H3K36R mutant (reminiscent of a set2-null mutant).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 80 publications
1
27
0
Order By: Relevance
“…While repair of the TS is slower in set2Δ mutant cells, loss of Set2 (or H3K36A) does not cause the same magnitude of repair defect as a rad26Δ mutant [40], suggesting Set2 functions to facilitate, but is not essential for, TC-NER. It has been recently reported that the Set2 homolog in S. pombe is also epistatic with NER factors in cells treated with methyl methanesulfonate (MMS), a DNA alkylating agent [53]. This observation can be explained by our finding that Set2 regulates TC-NER, since the TC-NER pathway may function to repair MMS-induced alkylation damage [54].…”
Section: Plos Geneticssupporting
confidence: 55%
See 1 more Smart Citation
“…While repair of the TS is slower in set2Δ mutant cells, loss of Set2 (or H3K36A) does not cause the same magnitude of repair defect as a rad26Δ mutant [40], suggesting Set2 functions to facilitate, but is not essential for, TC-NER. It has been recently reported that the Set2 homolog in S. pombe is also epistatic with NER factors in cells treated with methyl methanesulfonate (MMS), a DNA alkylating agent [53]. This observation can be explained by our finding that Set2 regulates TC-NER, since the TC-NER pathway may function to repair MMS-induced alkylation damage [54].…”
Section: Plos Geneticssupporting
confidence: 55%
“…It has been recently reported that the Set2 homolog in S . pombe is also epistatic with NER factors in cells treated with methyl methanesulfonate (MMS), a DNA alkylating agent [ 53 ]. This observation can be explained by our finding that Set2 regulates TC-NER, since the TC-NER pathway may function to repair MMS-induced alkylation damage [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid residues of the core histone proteins are heavily decorated with post-translational modifications (PTMs), particularly on the unstructured histone tail domains, and these modifications help to regulate chromatin compaction and govern the availability of docking sites for chromatin-modifying factors [ 1 , 6 ]. PTMs such as methylation, phosphorylation, acetylation, SUMOylation and ubiquitination occur via the transfer of chemical moieties onto specific residues of histone proteins [ 7 ] that engage in crosstalk and influence various DNA metabolic processes, including gene transcription [ 7 10 ], DNA damage repair [ 11 , 12 ], specialized chromosomal loci assembly [ 13 , 14 ], and cell cycle progression [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…H3K36me3 also precisely localizes the DNA mismatch recognition hMSH3 and hMSH6 proteins onto chromatin [ 11 ]. In fission yeast, new results suggest that H3K36me3 is the major form of methylation on H3K36 to mediate tolerance to MMS [ 12 ]. Histone H3K36 dimethylation appears to influence NHEJ [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%